STUDIES ON THE PROBABLE SOURCES OF FUNGAL INFECTION AND THE CONTROL MEASURES IN A FISH SEED FARM - GEORGE, J P; SEN, P K; VENUGOPAL, G; HINGORANI, H G (Fishery Technology, 2017)
The causes of mortality of fry of cultivable fishes in a fish seed farm were investigated. The mortality was due to fungal infection and the pathogen was Saprolegnia sp. The sources of infection were unhygienic breeding hapas, spawnery hapas in the cemented ponds, hatching jars and excess feeding. Application of one kg slaked lime foHowed by 75g of CuSo4 (l-0.5 p.p.m.) and 150g of KMno4 (2-1 p.p.m.) per each nursery (]_58m3water) controlled the pathogen.